Stevens’ handbook of experimental psychology - Pashler, Hal (John Wiley & Sons, 2002)
This revised and updated edition of the definitive resource for experimental psychology offers comprehensive coverage of the latest findings in the field, as well as the most recent contributions in methodology and the explosion of research in neuroscience. Volume Two: Memory and Cognitive Processes, focuses on the neurological and cognitive processes on topics such as memory, decision-making, spatial cognition, linguistics, reasoning, and concepts.